Bantuan Hukum Dalam Proses Penyidikan Tindak Pidana Narkotika Di Polda Sulawesi Selatan - Nurul Afiah; Imam Suyitno; Darman Manda (Phinisi Integration Review, 2022)
The rise of narcotics crime cases in South Sulawesi makes the suspects want to get legal assistance to be able to lighten their sentences. One of the rights of the suspect is to get legal assistance, especially for those who do not understand the law, even for those with lower middle social status. This study aims to (i) to see the process of legal assistance against narcotics crimes at the South Sulawesi Police, (ii) to see the process of determining the final determination of narcotics cases at the South Sulawesi Police. Meanwhile, the benefits of this research are (i) practical benefits and (ii) theoretical benefits. The method in this study is a type of qualitative descriptive research. The focus of this research is (i) looking at (i) the form of legal assistance in narcotics crime cases at the South Sulawesi Regional Police, (ii) the form of the final determination process of drug cases at the South Sulawesi Regional Police. Data collection techniques (i) observation, (ii) interviews and (iii) documentation. Data Analysis Techniques (i) Data Reduction, (ii) Data Presentation, (iii) Conclusion Drawing. The results of this study indicate that (i) the Legal Assistance Process for Narcotics Crimes at the South Sulawesi Police found that many suspects in narcotics cases felt they did not really need legal assistance like lawyers. This is because the suspects felt that their actions were very serious at the time of arrest in the field because of the evidence that was obtained. However, the police, in this case the South Sulawesi Regional Police, will continue to provide legal assistance or legal assistance to the suspects because it is a requirement in the trial in court later. (ii) The Final Determination of Narcotics Cases at the South Sulawesi Regional Police found that the police continued to escort the suspects until the narcotics case was decided in court. In addition, Narcotics cases are not always decided by imprisonment, but there are provisions of Law no. 35 of 2009 concerning Narcotics which can decide that suspects in Narcotics cases can be sentenced by means of rehabilitation.